Pengaruh Metode Jit Dan Kualitas Produk Terhadap Efesiensi Biaya Dengan Sistem Informasi Manajemen Sebagai Variabel Intervening. - Esti Sumirat; Anandio Triartomo; Nanda Pinandita; Djuma’iyah; Slamet Riyadi; Maria Yovita R Pandin (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
Companies need to make efficiency in order to get maximum profits, companies need to make production costs efficient, this can be done by using a management information system. This research investigates the influence of Just in time and product quality on management information systems. Also investigate whether management information systems are a good intervening variable in the relationship between research variables. This study conducted a survey of employees at UD Karya Logam Sidoarjo. Using saturated sampling method on 46 respondents. The data was then analyzed using Structural Equation Modeling. The findings show that Just in time and product quality make a positive contribution to management information systems. Research also proves that management information systems mediate the relationship between Just in time and product quality on production cost efficiency. This study contributes to management theory by using the framework of management information systems and cost efficiency.